Lower Flammability Limits – Experimental and Theoretical Determination Methods for Gaseous and Liquid Fuels. State of the Art - Marcin GRABARCZYK (Eksperymentalne i obliczeniowe metody oznaczania dolnej granicy wybuchowości paliw gazowych i płynnych – przegląd stanu wiedzy, 2016)
This work is an in-depth discussion of the experimental methods of lower flammability limit (LFL) determination and estimation in gases and the vapours of liquids. The focus here includes the dependences and drawbacks of each method. The work also outlines past research and discoveries that relate to the determination of explosion limits.
Keywords: dolna granica wybuchowości